2016
DOI: 10.1097/adm.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing a Two-stage Design to Investigate the Safety and Potential Efficacy of Monthly Naltrexone Plus Once-daily Bupropion as a Treatment for Methamphetamine Use Disorder

Abstract: Objectives This two-stage open-label pilot study evaluated the safety and potential efficacy of naltrexone plus bupropion as a pharmacotherapy for methamphetamine (MA) use disorder. Methods The study was conducted in two stages of recruitment across 3 sites; 20 participants were enrolled in Stage 1, and 29 participants were enrolled in Stage 2. Eight weeks of open-label pharmacotherapy with a combination of extended-release injectable naltrexone (XR-NTX; Vivitrol®) plus extended-release oral bupropion (BRP; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Furthermore, our participants were actively using methamphetamine, in contrast to an earlier trial of relapse prevention among amphetamine‐dependent people . Secondly, we studied XRNTX in isolation, whereas there may be benefit when the medication is combined with other agents .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our participants were actively using methamphetamine, in contrast to an earlier trial of relapse prevention among amphetamine‐dependent people . Secondly, we studied XRNTX in isolation, whereas there may be benefit when the medication is combined with other agents .…”
Section: Discussionmentioning
confidence: 99%
“…These results are better understood when examined in conjunction with the data presented in the primary outcome manuscript. Mooney et al (2016) showed that participants who responded to the medication (n ¼ 11) had high adherence rates and the selfreported (97.6%) and video-confirmed (95.2%) dosing adherence rates were very similar. In contrast, although participants who were medication nonresponders (n ¼ 38, including early withdrawals) also had high self-reported rates of adherence (92.1%), fewer doses were corroborated by video confirmation (83.4%).…”
Section: Discussionmentioning
confidence: 97%
“…Recognizing medication nonadherence as a source of serious confound and seeking to optimize oral medication adherence for a trial evaluating a promising combination pharmacotherapy for methamphetamine use disorder, we implemented a technology-assisted medication adherence component. To our knowledge, the ADAPT pilot study (Mooney et al, 2016) was the first trial that utilized a smartphone-enabled, video-confirmation strategy to remotely monitor and encourage oral medication adherence among people who use methamphetamine. The smartphone video dosing procedure was reported as feasible and well accepted by participants and staff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) or combination slow release naltrexone plus bupropion (Mooney et al . ). In general, all effects were either small to moderate or not replicated in more recent larger randomized control studies.…”
Section: Searching For the Holy Grailmentioning
confidence: 97%